The Role of Vitamin D in Combination Treatment for Patients With Rheumatoid Arthritis - Wu, Jianhong; Dong, Jianling; Li, Shilin; Luo, Jiaang; Zhang, Yu; Liu, Hong; Ni, Yuanpiao; Li, Xue; Zhou, Jun; Yang, Hang; Xie, Qianrong; Jiang, Xuejun; et al. (Frontiers in Medicine, 2020)
Background The aim of this study is to evaluate the clinical efficacy of vitamin D (VitD) supplementation in terms of response to treatment and improvement of disease activity in rheumatoid arthritis (RA). Methods This study analyzed 1180 RA patients’ records treated at Mianyang Central Hospital from February 2015 to July 2019. The patients were allocated into VitD group and control group based on their medical regimens. The outcome measures were primary efficacy, defined as treatment response-based EULAR response criteria in RA, and secondary efficacy, defined as improvement in disease activity indicators. Safety was evaluated according to the incidence of all-cause infections. Results At month 6, the primary efficacy revealed that there were 22.8% good responders and 19.0% moderate responders in the VitD group, and 22.3% good responders and 22.3% moderate responders in the control group; there were no differences between the two groups (p = 0.754). The similar primary efficacy outcomes were observed at months 3, 12 and >12. The secondary efficacy indicated that there were no differences in most indexes between the two groups at months 1, 3, 6, 12 and >12. The subgroups (based on baseline DAS28 (CRP), glucocorticoids use and disease duration) analysis results suggested that VitD group didn’t have advantage for treating RA. The incidence of infections was similar in the two groups. Conclusion VitD supplementation did not provide additional benefit for anti-rheumatic treatment. These data support the need for prospective, randomized, controlled trials to evaluate the role of VitD supplementation in treating RA.